Reanalyzing the Maia and McClelland (2004) Empirical Data: How Do Participants Really Behave in the Iowa Gambling Task? - Chiu, Yao-Chu; Huang, Jong-Tsun; Lee, We-Kang; Lin, Ching-Jen; Lin, Ching-Hung (Frontiers in Psychiatry, 2022)
Background Since 2007, the Iowa Gambling Task (IGT) has been a standardized clinical assessment tool for assessing decision behavior in 13 psychiatric/neurological conditions. After the publication of Maia and McClelland’s 2004 paper, there were two responses in 2005 from Bechara et al. and Maia and McClelland, respectively, discussing whether implicit emotion or explicit knowledge influences the development of foresighted decision strategies under uncertain circumstances (e.g., as simulated in the IGT). Methods and Results We reanalyze and verify the data obtained by Maia and McClelland in their 2004 study “What participants really know in the Iowa Gambling Task” and find that decision-makers were lured into shortsighted decisions by the prospect of immediate gains and losses. Conclusion Although the findings of this reanalysis cannot support any arguments concerning the effect of either implicit emotion or explicit knowledge, we find evidence that, based on the gain-loss frequency in the IGT, participants behave myopically. This is consistent with most IGT-related papers (58 out of 86) in Lee et al.’s (2020) cross-cultural review. Alternatively, under uncertain circumstances, there is probably no such thing as foresighted decision strategy irrespective of the proposed mechanisms of implicit emotion or explicit knowledge.